The ugly duckling of aphasia: cerebral venous sinus thrombosis as a mimic of TIA and stroke. Issue 1 (2nd January 2021) - Engelmann, Alexander; DiPastina, Katherine; Liu, Tianyu
ABSTRACT: Cerebral venous sinus thrombosis may present with transient aphasia and focal seizure-likeactivity mimicking a TIA or stroke. In this case, the patient's presentation was further complicated by non-diagnostic CT findings, which can be common in up to 27% of cases [1]. An 86-year-old right-handed male with a history of colon adenocarcinoma status post resection and recent surgery for right sphenoid wing meningioma presented to the ED with transient episodes of fluent aphasia lasting approximately 10 minutes and one episode of involuntary right-hand clenching, both of which resolved spontaneously and were concerning for possible TIA. Non-contrast head CT, CTA head and neck, and CT perfusion studies showed non-opacification of the left transverse and sigmoid sinuses, but no perfusion defects. Subsequent MRI brain with gadolinium revealed a new left transverse sinus thrombus. EEG was without epileptiform features. For the 13-day remainder of his hospitalization the patient received low molecular weight heparin for anticoagulation, and he experienced no recurrence of his symptoms. He was discharged on apixiban and levetiracetam to follow-up for possible tumor recurrence. Cerebral venous sinus thrombosis can present with stroke-like symptoms, and CT perfusion studies can be normal. CT venography, MRI with gadolinium, and MR venography are sensitive imaging modalities for diagnosing dural sinus thrombosis and should be considered, especially for patients with hypercoagulable risk factors, MR venography being the most sensitive, preferred modality [2]. Additionally, it is important to recall the laterality of focal symptoms, as a history of cerebrovascular disease can be a confounding factor in diagnosis.